Studi Kualitatif Terkait Pengalaman Membangun Kembali Kepercayaan dan Menyembuhkan Trauma Seorang Wanita yang Menjadi Korban Perselingkuhan - Sasha Indara Cendani; Hardani Widhiastuti; Margaretha Maria Shinta Pratiwi (Jurnal Impresi Indonesia, 2025)
Infidelity committed by a man will have a negative impact on his partner, especially on their relationship, the problem of infidelity also has a fairly complicated and vulnerable process so it must be handled immediately because it has two possibilities between separation or forgiveness, but forgiveness also has 3 possibilities, namely forgiving and responding to the cheating behavior, or forgiving but changing the attitude of the cheated on, or even some who forgive and continue to behave normally. Because women will not fully forgive but still have a flaw in trust and even trauma (trust issue) to men who cheat. So the purpose of this study is so that all women who read my research can have the spirit to rise again from trauma and want to try to give men the opportunity to improve harmony in relationships.